The Shoot in Isaiah 11: A Subversive Hybrid Figure - Sam, Philip (Old Testament essays, 2025)
Isaiah 11, also known as the oracle of the "shoot of Jesse," imagines the ushering of an ideal age. The production of the book of Isaiah, including its multiple redactions, in the material circumstances of the subjugation of Israel under successive empires, makes it necessary to ask whether or how the text engages with its imperial milieu. What kind of figure does the "shoot of Jesse" represent in its imperial landscape? What kind of rule is imagined by the Shoot Oracle? This article engages with these questions by employing Homi Bhabha’s concept of hybridity and argues that the poetic celebration of the "shoot of Jesse" presents a mimetic/hybrid figure and articulates an in-between space that subverts the imperial discourse as well as nationalistic hegemonic overtures of the Davidic dynasty.